Obraz tęsknoty za Odessą-Mamą (na przykładzie filmów „Odessa!... Odessa!” Michale Boganim, „Wszystko jest iluminacją” Lieva Schreibera oraz „Likwidacja” Siergieja Ursuljaka) - Marta Siekierska (Studia Rossica Posnaniensia)
The article examines the process of longing for Odessa-Mama on the basis of Michale Boganim’s Odessa…Odessa!, Liev Schreiber’s Everything is illuminated and Sergey Ursulyak’s Liquidation. In this paper particular attention is devoted to the terms Odessan myth and Odessan text that are key elements of analysed movies and contribute to the nostalgic portrayal of Odessa.